Captain John Smith - Kline, Trish (Vero Beach, FL : Rourke, 2002)
Presents a brief biography of explorer John Smith, the man who led the first English colony in the New World.
Includes bibliographical references and index.
AR
3.
1-5.
Accelerated Reader
Keywords: Smith, John, -- 1580-1631.; Explorers -- Biography; Jamestown (Va.) -- History; Virginia -- History; United States -- History -- 1600-1775, Colonial period